2007
DOI: 10.1007/s12170-007-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical activity and fitness in the prevention and treatment of metabolic syndrome

Abstract: The metabolic syndrome is a significant public health problem that is increasing in prevalence throughout the developed and the developing world. Lifestyle changes are recommended as the primary tool in the prevention and treatment of risk factor clustering. Physical activity should be considered a cornerstone of prevention and treatment efforts related to metabolic syndrome. Considerable evidence supports that physically inactive men and women are at increased risk for prevalent and incident metabolic syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“… 22 , 23 Individuals who engage in physical activity were 53% less likely to develop MetS as compared with those who did not engage in physical activity. 24 A study in Cameroon also reported that regular physical activity was significantly associated with lower development of MetS. 25 A study conducted among working adults in Addis Ababa, Ethiopia reported that men who engaged in higher physical activity decreased the occurrence of MetS by 44% as compared to those engaged in a low level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Individuals who engage in physical activity were 53% less likely to develop MetS as compared with those who did not engage in physical activity. 24 A study in Cameroon also reported that regular physical activity was significantly associated with lower development of MetS. 25 A study conducted among working adults in Addis Ababa, Ethiopia reported that men who engaged in higher physical activity decreased the occurrence of MetS by 44% as compared to those engaged in a low level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies prove that regular physical activity is the cornerstones of prevention of metabolic syndrome and risk factors of cardiovascular disorder and diabetics Miletus. The individual with physical activities are 53% less risk for metabolic syndrome than those who didn’t do physical activities [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Health and Nutrition Examination Survey (NHANES) 1999–2004, approximately 36% of the United States (U.S.) adult population have metabolic syndrome as classified by the AHA/NHLBI criterion 16. Recent studies have reported that physical activity level 1720 and physical fitness 21, 22 are associated with lower prevalence and incidence of metabolic syndrome and individual CVD risk factors (e.g., high blood pressure, insulin resistance, abdominal adiposity, and dislipoproteinemia). Sedentary time and lack of exercise have also been related to metabolic syndrome and individual CVD risk factors in populations across the globe 1114.…”
Section: Introductionmentioning
confidence: 99%